(3QSGdI GdQTO hGdgOGjIs - (3ESeGYjd Hf eMeO GdJejeis; (3CHh EHQGgje ESeGYjd Hf eMeO Hf MGeO GdJejej,J (B420 (3g` s
(3ChdgG (B:s
(3fU GdeLJHi hEOQjS GdReGf s
(3BNQgG (B:s
(3fU gPg GdQSGdI GdJi hVYJgG hSejJgG GdQTO hGdgOGjIq s
(3Vef eLehY , JQJjHgG (B: 25s
(3GdeDda ef OYGI GdHGWfjIs
(3hdg YfO GdOQRjI ebGe cHjQs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJhMjO hGdedd hGdfMds